Effect of HCG-Triggered Ovulation on Pregnancy Outcomes in Intrauterine Insemination: An Analysis of 5,610 First IUI Natural Cycles With Donor Sperm in China - Wan, Ji-Peng; Wang, Zhen-Jing; Sheng, Yan; Chen, Wei; Guo, Qing-Qing; Xu, Jin; Fan, Hua-Rui; Sun, Mei (Frontiers in Endocrinology, 2020)
Objective: To evaluate the effect of human chorionic gonadotropin (hCG) trigger ovulation on pregnancy outcomes in natural IUI cycles with donor sperm. Methods: This retrospective cohort study included 5,610 first-natural IUI cycles with donor sperm in infertile couples during the period from January 2012 to December 2017. To control for other confounding factors, our analysis was restricted to normo-ovulatory women without tubal infertility. The main outcome measure was live birth rate; the secondary outcomes included rates of clinical pregnancy and miscarriage. Results: In the crude analysis, both the clinical pregnancy (27.40 vs. 22.73%; P = 0.001) and live birth rates (24.52 vs. 20.13%; P = 0.007) were significantly higher for the hCG group than for the spontaneous LH group. After adjustment for a number of confounding factors, the reproductive outcomes were still significantly worse for the spontaneous ovulatory group. Conclusions: Among women undergoing natural cycle IUI with donor sperm, hCG triggered ovulation for timing insemination offers beneficial impacts on both clinical pregnancy rates and live birth rates.